-9m+11=-8+4

Simple and best practice solution for -9m+11=-8+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9m+11=-8+4 equation:


Simplifying
-9m + 11 = -8 + 4

Reorder the terms:
11 + -9m = -8 + 4

Combine like terms: -8 + 4 = -4
11 + -9m = -4

Solving
11 + -9m = -4

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -9m = -4 + -11

Combine like terms: 11 + -11 = 0
0 + -9m = -4 + -11
-9m = -4 + -11

Combine like terms: -4 + -11 = -15
-9m = -15

Divide each side by '-9'.
m = 1.666666667

Simplifying
m = 1.666666667

See similar equations:

| Q=r-s/s | | 4c(c+3)=84 | | 121=(x+6)(20-4x) | | 4m-8=44 | | 2k+1=k+5 | | 1/5(10x-5)=1/4(10x-8) | | y^2-23y-28=0 | | -v^2+11v-28=0 | | 4+9x^2=40 | | -u^2+8u-12=0 | | 6n^2=8n+11 | | 3x^2+14x+144=0 | | A+3b+70=100 | | x^2+14x+144=0 | | 66000=3x^2+4x+2 | | 25s^4t^7/5s^3t^9 | | 8xy-6xy+2xy= | | 62=3y+17 | | 0=-2/((m-2)(m-4)) | | x+3x-24= | | 0=-2/(m-2)(m-4) | | 3y^2+2x-3=0 | | 36k^2=49 | | x-8x+15= | | 3x-10x=0 | | 27x^4-72x^2+8x+36=0 | | x+20x+36= | | -8-(x/2)=-10 | | y+112=805 | | 29n=986 | | x/5-8=1 | | 835=k+35 |

Equations solver categories